A new path to design near-infrared persistent luminescence materials using Yb3+-doped rare earth oxysulfides. (15th April 2019) - Machado, Ian Pompermayer; Pedroso, Cássio Cardoso Santos; Carvalho, José Miranda de; Teixeira, Verônica de Carvalho; Rodrigues, Lucas Carvalho Veloso; Brito, Hermi Felinto
Abstract: RE2 O2 S:Yb 3+ and RE2 O2 S:Yb 3+, Ti, Mg 2+ near-infrared persistent luminescence materials (RE 3+ : La, Gd, Y) were designed based on the efficient red-emitting RE2 O2 S:Eu 3+, Ti, Mg 2+, due to the similar ground state level positions between Eu 3+ and Yb 3+ . The Y2 O2 S:Yb 3+, Ti, Mg 2+ showed the longest near-infrared ( 983 nm) persistent luminescence time ( 1 h) when excited at the charge transfer transition, demonstrating that Ti, Mg 2+ co-doping enhances the persistent luminescence only for the Y2 O2 S host. The unprecedented relationship between Eu 3+ and Yb 3+ persistent luminescence opens a new path in the systematic design of efficient Yb 3+ -activated persistent luminescence materials e.g. Y2 O2 S:Yb 3+, Ti, Mg 2+, which present potential for photonic applications such as bioimaging probes. Graphical abstract: Unlabelled Image